"I can't breathe": Lay conceptualizations of racism predict support for Black Lives Matter. (April 2021) - Miller, Stuart S.; O'Dea, Conor J.; Saucier, Donald A.
Abstract: We examined how individual differences in White individuals' lay conceptualizations of racism are related to support for Black Lives Matter and protests against inequality. In our study, a more systemic conceptualization of racism, along with other individual differences (e.g., beliefs about racial discrimination and White privilege, self-presentational concerns about appearing racist) significantly predicted greater support for the Black Lives Matter movement and specific actions (e.g., protesting, political pressure) used to bringing about racial equality. Further, these ideologies predicted support for both White people and People of Color working to address the issue, highlighting the strength people perceive in allies against inequality. However, those who reject these beliefs may seek to limit the methods by which individuals affected by racial inequality are permitted to use in challenging that inequality. Highlights: Conceptualizations of racism as a systemic problem predicted support for Black Lives Matter. Conceptualizing racism as merely individual acts may undermine support for collective action. Perceptions of racism are related to support for allyship in addressing racial inequality.